Curated Archiving of Research Software Artifacts: Lessons Learned from the French Open Archive (HAL) - Roberto Di Cosmo; Morane Gruenpeter; Bruno Marmol; Alain Monteil; Laurent Romary; Jozefina Sadowska (International Journal of Digital Curation, 2020)
Software has become an indissociable support of technical and scientific knowledge. The preservation of this universal body of knowledge is as essential as preserving research articles and data sets. In the quest to make scientific results reproducible, and pass knowledge to future generations, we must preserve these three main pillars:  research articles that describe the results, the data sets used or produced, and the software that embodies the logic of the data transformation.